An Evaluation of the Accounting Information System of BUMDes Maju Rahayu - Kustiyono Kustiyono (International Journal of Economics and Management Sciences, 2025)
Village-Owned Enterprises (BUMDes) function as important economic institutions that contribute to enhancing the welfare and independence of rural communities. BUMDes Maju Rahayu, as one of the rapidly developing BUMDes, requires a reliable and effective accounting information system to support transparent and accountable financial management. This study aims to evaluate the implementation of the accounting information system at BUMDes Maju Rahayu using a qualitative approach with a case study method. Data collection was conducted through in-depth interviews with BUMDes managers and direct observation of financial recording and reporting processes. The findings reveal that the existing accounting system still faces several challenges, including incomplete documentation, limited internal control, and dependence on manual bookkeeping. These issues hinder the accuracy and timeliness of financial information. The study recommends capacity-building for human resources, adoption of technology-based accounting systems, and strengthening of internal control procedures to improve financial management quality and organizational performance in BUMDes operations.